PERAN PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN JATI DIRI KEBANGSAAN SISWA SMK NURUL HIDAYAH BONDOWOSO MELALUI PENDEKATAN MULTIKULTURAL - Miftahus Salam (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
This research aims to discuss multicultural education in forming the national identity of students at Nurul Hidayah Bondowoso Vocational School, as well as various approaches that can be applied, as well as challenges and opportunities in implementing multicultural education. This research uses a qualitative approach to analyze the role of Islamic religious education in the formation of national identity through multicultural education at SMK Nurul Hidayah Bondowoso. The collected data will be analyzed including: data reduction, data filtering and drawing conclusions. Meanwhile, to ensure data validity, this research will use triangulation, member checking, and audit trail. The results of the research show that multicultural education in the formation of national identity for students at SMK Nurul Hidayah Bondowoso has been implemented optimally through Islamic religious education with teaching and learning activities in the classroom and integrated with activities outside the classroom such as work degree activities, religious and national seminars, congregational prayers. 'ah, community service work at the end of every month, eating together at the commemoration of National Teachers' Day, a program for changing class administrators at each class increase is chosen through consensus deliberation. Extracurricular activities such as hadrah arts, futsal, and scouting. Meanwhile, indicators of the success of multicultural education in forming students' national identity are shown by students' understanding of the values ​​of democracy, equality, togetherness/mutual cooperation, and tolerance. This understanding is proven by students' actions in daily behavior.